2022
DOI: 10.1002/pc.26487
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and properties of silicone grafted epoxy/acrylonitrile butadiene styrene/graphene oxide nanocomposite with high adhesion strength and thermal stability

Abstract: To improve thermal, mechanical and adhesion properties, epoxy resin was modified with methyl phenyl silicone (MPS), acrylonitrile butadiene styrene (ABS) and graphene oxide (GO). In order to increase compatibility and stability, MPS intermediate was grafted on epoxy resin through condensation reaction. Transmission electron microscopy images showed well dispersion of GO particles in the system proving successfully preparation of the MPS grafted epoxy/ABS/GO nanocomposite. Single lap shear strength for steel‐ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 99 publications
(163 reference statements)
0
12
0
Order By: Relevance
“…It is reported that some rigid nanoparticles such as nanoclays, [26] nanosilica, [27] graphene oxide, [28][29][30][31] and nanotubes [32] can reinforce epoxy resin. Zhang et al improved the tensile properties of aliphatic epoxy resins by adding multi-walled carbon nanotubes treated with mixed acid.…”
Section: Introuductionmentioning
confidence: 99%
“…It is reported that some rigid nanoparticles such as nanoclays, [26] nanosilica, [27] graphene oxide, [28][29][30][31] and nanotubes [32] can reinforce epoxy resin. Zhang et al improved the tensile properties of aliphatic epoxy resins by adding multi-walled carbon nanotubes treated with mixed acid.…”
Section: Introuductionmentioning
confidence: 99%
“…TEM images of nanocomposite samples containing 0.1 wt.% GO that is published in our previous work showed well dispersion of GO in the epoxy matrix. GO nano sheets tend to agglomerate when the amount of GO increased to 0.2 wt.% 16 . High strength of GO sheets, good compatibility as well as well dispersion of them in epoxy matrix are responsible for improving of the impact strength in specimen containing 0.1 phr GO.…”
Section: Resultsmentioning
confidence: 99%
“…GO nano sheets tend to agglomerate when the amount of GO increased to 0.2 wt.%. 16 High strength of GO sheets, good compatibility as well as well dispersion of them in epoxy matrix are responsible for improving of the impact strength in specimen containing 0.1 phr GO.…”
Section: Izod Impact Strengthmentioning
confidence: 99%
See 2 more Smart Citations